The Bakhtin Reader / Selected Writings of Bakhtin, Medvedev, Voloshinov - Edward Arnold; Morris Pam (1994)
An invaluable introduction to a complex and scattered body of work. Acknowledgements, Introduction, Dialogic Discourse, The Heteroglot Novel, Literature as Ideological Form, Carnival Ambivalence, Bibliography, Index.